Garden suburbs and the picturesque. historiographic review (2009)
This article grew from my particular interest in argentinian romantic suburbs. From there I have decided to explore the bases of the particular relationship between the suburbs and the picturesque aesthetics. Along the next lines, I will set the principles of the Garden City, and it´s transformation into the concept of Garden Suburb after the settlement of the first garden city, by the architects Raymond Unwin and Barry Parker. The second part of the work deals with a varie ty of historiographic sources –Art History ; Architecture Studies and Urban History– in relation with the priority themes concerning the modern suburbs, Garden City, Garden Suburbs and Picturesque. I will try to set a path from the theories built by historians at the early years of the XXth century, to the latest reviews introduced in this area of studies.